AANL (Agrocybe aegerita lectin 2) is a new facile tool to probe for O-GlcNAcylation. (19th March 2018) - Liu, Wei; Han, Guanghui; Yin, Yalin; Jiang, Shuai; Yu, Guojun; Yang, Qing; Yu, Wenhui; Ye, Xiangdong; Su, Yanting; Yang, Yajun; Hart, Gerald W; Sun, Hui
Abstract: O-linked N -acetylglucosamine ( O -GlcNAcylation) is an important post-translational modification on serine or threonine of proteins, mainly observed in nucleus or cytoplasm. O -GlcNAcylation regulates many cell processes, including transcription, cell cycle, neural development and nascent polypeptide chains stabilization. However, the facile identification of O -GlcNAc is a major bottleneck in O -GlcNAcylation research. Herein, we report that a lectin, Agrocybe aegerita GlcNAc-specific lectin (AANL), also reported as AAL2, can be used as a powerful probe for O -GlcNAc identification. Glycan array analyses and surface plasmon resonance (SPR) assays show that AANL binds to GlcNAc with a dissociation constant (KD) of 94.6 μM, which is consistent with the result tested through isothiocyanate (ITC) assay reported before (Jiang S, Chen Y, Wang M, Yin Y, Pan Y, Gu B, Yu G, Li Y, Wong BH, Liang Y, et al. 2012. A novel lectin from Agrocybe aegerita shows high binding selectivity for terminal N -acetylglucosamine. Biochem J. 443:369–378.). Confocal imaging shows that AANL co-localizes extensively with NUP62, a heavily O -GlcNAcylated and abundant nuclear pore glycoprotein. Furthermore, O -GlcNAc-modified peptides could be effectively enriched in the late flow-through peak from simple samples by using affinity columns Sepharose 4B-AANL or POROS-AANL . Therefore, using AANL affinity column, we identified 28 high-confidence O-linked HexNAc-modified peptides mapped on 17 proteins involving diverse cellular progresses, including transcription, hydrolysis progress, urea cycle, alcohol metabolism and cell cycle. And most importantly, major proteins and sites were not annotated in the dbOGAP database. These results suggest that the AANL lectin is a new useful tool for enrichment and identification of O -GlcNAcylated proteins and peptides.